Measuring the importance of oil-related revenues in total fiscal income for Mexico - Reyes Loya, Manuel Lorenzo; Blanco González, Lorenzo (IPC Science and Technology Press, 2008)
Revenues from oil exports are an important part of government budgets in Mexico. A time-series analysis is conducted using monthly data from 1990 to 2005 examining three different specifications to determine how international oil price fluctuations and government income generated from oil exports influence fiscal policy in Mexico. The behavior of government spending and taxation is consistent with the spend-tax hypothesis. The results show that there is an inverse relationship between oil-related revenues and tax revenue from non-oil sources. Fiscal policy reform is urgently needed in order to improve tax collection as oil reserves in Mexico become more and more depleted. © 2008 Elsevier B.V. All rights reserved.